Implicit currency carry trades of companies - Oliver Entrop; Fabian U. Fuchs (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2020)
The currency carry trade (CCT) strategy - borrowing in low-interest-rate currencies and investing in high-interest-rate currencies - has been found to generate excess returns that cannot be explained by common risk factors. We argue that companies implicitly execute carry trades, when they have input costs and sales in countries with differing interest rate levels. Consequently, the equity of companies that are not fully hedged against foreign exchange rate changes should be sensitive to returns from currency carry trades. Analyzing a broad sample of US firms, our contribution to the literature is twofold: (i) Based on an APT approach we find a risk premium for implicitly executed currency carry trades in equity returns. (ii) We examine the influence of various company-specific characteristics and find that a company's size and liquidity have the most significant impact on its sensitivity to currency carry trade returns.
Keywords: F31; G32; G15; 650; carry trade; hedging; exchange rate exposure; uncovered interest parity